Analisis Penyimpangan Perilaku Sopan Santun pada Remaja di Desa Tomuan Kecamatan Siantar Timur - Ayu Rukia Siburian; Vidya Dwi Amalia Zati (EduInovasi: Journal of Basic Educational Studies, 2025)
This study was conducted with the aim of finding out simple behavioral deviations in adolescents in Tomuan Village. The method used in this study is a qualitative research method with 4 adolescents in the Permata community aged 13-18 years in Tomuan, East Siantar District. The data obtained in this study was measured using data collection techniques with observation, interviews and documentation. Data are analyzed using data reduction, data presentation, and conclusions drawn. The results of this study show that there are three deviations of polite behavior in adolescents in Tomuan village, namely: 1) deviations in polite behavior in speaking by speaking several rude languages such as the words anjir, bachelor, bodat with fellow socialization, but if talking to parents, still prioritize polite grammar, 2) deviations in dressing behavior by using impolite clothes such as wearing tread clothes,    Mini skirts, mini pants, wearing shirts without buttons closed, because as they say dress as they are their custom due to the development of the times and 3) deviations in behavior or manners or behavior with the rarity of teenagers saying thank you, apologizing, or helping others. As for the factors that cause deviations in polite behavior in adolescents are external factors and internal factors, it is known that these two factors play a major role in changes in polite behavior in speech, dress and behavior in adolescent behavior or behavior. Because of these external factors and internal factors, adolescents meet new people who all have different polite behaviors, so if there is only one different polite behavior of adolescents, it can make adolescents follow new things they see and hear.